Influence of time of residence on the sense of community and satisfaction with life in immigrants in Spain: The moderating effects of sociodemographic characteristics - Millán-Franco, Mario; Gómez-Jacinto, Luís; Hombrados-Mendieta, Isabel; García-Martín, Miguel Ángel; García-Cid, Alba (Wiley, 2019)
Migration is an example of adaptation with enduring effects over time and in different cultures. Few studies have analyzed the effect of the sense of community (SOC) on satisfaction with life (SWL) over time while taking into account the moderating effects of sociodemographic char acteristics. We propose a model that explains the influence of time of residence on the SOC and SWL. It was hypothesized that the SOC has a positive influence on SWL and that SWL is moderated by sociodemographic characteristics and cultural differences. Participants were 2,211 immigrants residing in Malaga (Spain). Results show a positive association between years of residence and the SOC and the SWL. A positive association was found between the SOC and SWL. This study shows the relevance of analyzing the moderating effects of sociodemographic characteristics in different immigrant groups rather than according to the migration process as a whole to develop specific intervention strategies.
Keywords: Calidad de vida; Comunidad; Inmigrantes - España; Immigration; Satisfaction with life; Sense of community; Sociodemographic characteristics; Time of residence